Board Independence, Corporate Social Responsibility and Firm Performance: Evidence from China - Jaidi, Junainah; Wenhao, Miao; Mohidin, Rosle (UUM Press, 2022)
The purpose of this paper was to investigate the relationship between board independence and the firm performance of Chinese firms listed in the Shanghai Stock Exchange, under the moderating role of Corporate Social Responsibility (CSR). A total of 860 firm-year observations over a period of ten years, that is from 2010 to 2019 was collected. The panel data regression technique was employed to analyze the data and determine the relationship between board independence and the firm performance of the Chinese firms under investigation. After a robustness check, the empirical results showed that the level of the CSR moderated (reduced) the positive relationship between board independence and firm performance. Therefore, the results seemed to imply that although the CSR has been seen as a useful business strategy, the level of the CSR in China still needed to be improved. In order to improve firm performance through practicing the CSR, the Chinese government and enterprises should be encouraged to continuously improve the level of the CSR.